2018
DOI: 10.1080/16066359.2018.1434156
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive defusion versus experiential avoidance in the reduction of smoking behaviour: an experimental and preliminary investigation

Abstract: Background: Brief procedures that reduce smoking behaviour may be useful in reaching the many people that do not seek help for smoking addiction. Objectives: The current study aimed to determine if one component of Acceptance and Commitment Therapy (ACT), cognitive defusion, could be useful in reducing smoking behaviour in a sample of students. Methods: The study employed a between-subjects three-arm design. For one week, participants were asked to reduce their cigarette consumption. To aid them in their reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…As an example, Hooper, Sandoz, et al (2012) showed that participants who were instructed to suppress thoughts of chocolate for a week experienced a behavioral rebound on a subsequent taste test, where they ate significantly more chocolate than a group that had been instructed to use the acceptance-based technique of cognitive defusion. Similar studies have found that acceptance-based techniques are more effective than thought suppression, or similar strategies that serve an experiential avoidance function, for reducing smoking behavior (Hooper et al, 2018), in mitigating learned helplessness (Hooper & McHugh, 2013b), and for dealing with spider phobia (Hooper et al, 2011). Findings thus support the use of acceptance-based mental strategies over thought suppression and similar strategies for dealing with aversive thoughts and as a self-control strategy when attempting to resist temptations.…”
Section: Cognitive Control Of Mental States As Experiential Avoidancesupporting
confidence: 61%
See 1 more Smart Citation
“…As an example, Hooper, Sandoz, et al (2012) showed that participants who were instructed to suppress thoughts of chocolate for a week experienced a behavioral rebound on a subsequent taste test, where they ate significantly more chocolate than a group that had been instructed to use the acceptance-based technique of cognitive defusion. Similar studies have found that acceptance-based techniques are more effective than thought suppression, or similar strategies that serve an experiential avoidance function, for reducing smoking behavior (Hooper et al, 2018), in mitigating learned helplessness (Hooper & McHugh, 2013b), and for dealing with spider phobia (Hooper et al, 2011). Findings thus support the use of acceptance-based mental strategies over thought suppression and similar strategies for dealing with aversive thoughts and as a self-control strategy when attempting to resist temptations.…”
Section: Cognitive Control Of Mental States As Experiential Avoidancesupporting
confidence: 61%
“…Additionally, cognitive control in the form of both thought suppression (Hennings et al, 2021), and attentional avoidance (O'Malley & Waters, 2018) during a fear extinction procedure have been shown to detrimentally impact fear extinction, similar to would be expected in relation to behavioral avoidance (Cornwell et al, 2013;Rattel et al, 2017). Hooper and colleagues (Hooper, 2010;Hooper et al, 2018;Hooper, Saunders, et al, 2010;Hooper, Villatte, et al, 2010;Hooper & McHugh, 2013a, 2013b have investigated the consequences of thought suppression and similar cognitive control strategies from an experiential avoidance perspective. Their account is grounded in the theoretical framework of Relational Frame Theory (Hayes et al, 2001), a contemporary behavior analytic theory of language and cognition.…”
Section: Cognitive Control Of Mental States As Experiential Avoidancementioning
confidence: 99%
“…Importantly, the mean number of cigarettes smoked per day also statistically significantly decreased in the Flexiquit compared to control group even among those individuals who did not quit smoking at postintervention. Therefore, even for participants who did not manage to fully quit at post, there was a trend towards decreasing the amount of cigarettes smoked per day in the intervention group, potentially bringing this group closer to completely quitting in the future [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…To verify the proposed method, a real case application is set up in this section. This paper is employed six smoking causes among Jordanian as the alternatives which are Parental Influence (A1) [10]- [12], Film Star Attraction (A2) [13]- [16], Feel More Adult (A3) [17]- [21], Look Cool/Fashionable (A4) ( [22]- [24]), Weight Control (A5) [25]- [28] Parent Neglect (A6) [29]- [31]. Based on six alternatives, four criteria were considered in this studu.…”
Section: Assessment On Smoking In Jordan and Resultsmentioning
confidence: 99%